Assessment of Sociolinguistic and Religious Effects of Anti-Islamic Expressions among Yoruba-Muslims of Selected Southwestern States in Nigeria (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Language and religion are cardinal aspects of human existence. It is also almost impossible to separate a language from its cultural and traditional attachments; the experience enshrined in Yoruba, a major Nigerian language, whose core practices take cue from traditional approach of worshipping. Hence, this study aims to analyse some expressions uttered by Yoruba-Muslims which are against their own religion, to sociolinguistically examine the antagonistic effects of such expressions to Islamic faith, and to proffer ways to guide against them. The research tool used is Dell Hymes’ (1974) Ethnography of SPEAKING theory while the Yoruba data were interpreted using Baker’s (2018) ‘textual' and 'pragmatic' equivalence approach. The population comprised three (3) South-western (Yoruba-speaking) states of Nigeria which are Osun, Oyo, and Lagos States; and part of the North-central (Ilorin) where Islam is the main religion and Yoruba language is dominantly spoken. It was revealed through the settings of the utterances that surprisingly, educated Yoruba-Muslims use the expressions mostly as shown in the 49 (61.25%) respondents from educational environments against 31 (38.75%) from domestic localities. However, there is a slight difference in the range of participants from both genders in the use of the utterances as 45 male respondents representing 56.25% and 35 female respondents representing 43.75% proof their difference. It is recommended that linguistic researches should be carried out on anti-Christian expressions in order to afford for sanctity of the society through the power of language without fear or favour of one religion over another. In conclusion, Yoruba-Muslims must navigate these complexities of the richness of Yoruba traditions and the significant challenges it poses to their Islamic orthodoxy and effective communication to ensure that their cultural expressions align positively with Islamic principles.
Keywords: Ethnography of SPEAKING; Islam; Religion; Sociolinguistics; Yoruba-Muslims